UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 021 MUARA LANGSAT MELALUI PENGGUNAAN METODE DEMONSTRASI DAN ALAT PERAGA - Warsinah Warsinah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
Research on efforts to improve the learning outcomes of mathematics students class V SDN 021 Muara Langsat through the use of demonstration methods and props held in the even semester 2014/2015 with the aim to know the improvement of student learning outcomes through demonstrations and props on subjects mathematics class V SDN 021 Muara Langsat. The data collected in this research is teacher activity data and student activity data in two cycles. Each cycle has four stages: planning, action execution, observation and reflection. The subjects of this study are students of grade V SDN 021 Estuary Langsat which amounted to 19 students consisting of 10 men and 9 women. This study was conducted on the basic competence to describe the nature of the wake flat. The results obtained from this research is the use of demonstration methods and props can improve student learning outcomes.